2008
DOI: 10.1016/j.rmed.2008.07.018
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and follow-up to noninvasive home mechanical ventilation: Ambulatory versus hospital

Abstract: HMV improved arterial blood gases and quality of life in patients with restrictive ventilatory disorders. Arterial blood gases were better in the ambulatory group and the quality of life was similar in both groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Despite this, consensus on how best to implement NIV for treatment-naive users is lacking [1,5,6]. A variety of implementation methods have been reported, ranging from inpatient hospital assessments to ambulatory or home-based models [1,[7][8][9][10][11]. Reports have also described varying combinations of clinical assessments and other measures that may assist with treatment initiation and monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, consensus on how best to implement NIV for treatment-naive users is lacking [1,5,6]. A variety of implementation methods have been reported, ranging from inpatient hospital assessments to ambulatory or home-based models [1,[7][8][9][10][11]. Reports have also described varying combinations of clinical assessments and other measures that may assist with treatment initiation and monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…As proved by foreign studies [6,[34][35][36][37][38][39][40][41][42], HMV is associated with the benefits of longer survival and improved quality of life. Assessing health-related quality of life is becoming an increasingly important criterion in research and healthcare, especially in the evaluation of the cost-benefit ratio of medical devices or patients with chronic, incurable disorders [37,41].…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, a cost-utility analysis examining its benefits in terms of quality of life was selected to evaluate HMV and MV variants in patients with ALS. On the basis of the mentioned studies [6,[34][35][36][37][38][39][40][41][42] and the opinion of experts, the assumption of a 10% reduction in the quality of life of a patient in a hospital environment was chosen for the cost-utility analysis. The value of the reduction was subsequently varied in the sensitivity analysis and changed the significance of ICUR as the only input, and HMV as the only dominant variant became cost-effective, if we assume that both variants fall below the willingness to pay threshold as they are already covered.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, hospitalization is expensive, there may be waiting lists, and it has not been conclusively demonstrated that this policy leads to better compliance with the prescription [11,12]. Thus, some authors prefer to carry out NIMV adaptation in the sleep laboratory [13,14], whereas others advocate ambulatory adaptation in an outpatient clinic or the patient's home [11,12,15].…”
Section: Introductionmentioning
confidence: 99%